The detection of ovine herpesvirus-2 in reservoir host of malignant catarrhal fever in Indonesia by means of polymerase chain reaction - Agus Wiyono (Jurnal Ilmu Ternak dan Veteriner, 1999)
Malignant catarrhal fever (MCF) is a fatal disease affecting large ruminants, some wild animals and pigs. Ovine herpesvirus- 2 (OHV-2) is the causal agent of sheep-associated MCF (SA-MCF). In Indonesia, sheep is epidemiologically implicated in the occurrence of MCF. Providing a sensitive and specific molecular biological technique, i.e. polymerase chain reaction (PCR), a wide range of MCF aspects on molecular level have been developed. The PCR has been successfully used to detect OHV-2 fragment in sheep samples such as peripheral blood leucocytes (PBL) of sheep, nasal secretion of a sheep lamb, and organs of some sheep lambs. Fragment of OHV-2 was also detected in PBL of goats from some areas in Indonesia but not in PBL of pigs from Bali. These results suggest that sheep and sheep lambs are the potential reservoir hosts of MCF in Indonesia, while the role of goats as reservoir host of MCF has yet to be determined.   Key words : Ovine herpesvirus-2, polymerase chain reaction, reservoir host, malignant catarrhal fever, Indonesia